Valsalva maneuver to visualize the closed hypopharyngeal space during transoral endoscopy using a novel dedicated mouthpiece. Issue 1 (2nd December 2018) - Kato, Minoru; Hayashi, Yoshito; Takehara, Tetsuo
Abstract : Watch a video of this article